The transcriptomic and epigenetic map of vascular quiescence in the continuous lung endothelium - Schlereth, Katharina; Weichenhan, Dieter; Bauer, Tobias; Heumann, Tina; Giannakouri, Evangelia; Lipka, Daniel; Jaeger, Samira; Schlesner, Matthias; Aloy, Patrick; Eils, Roland; Plass, Christoph; Augustin, Hellmut (eLife, 2018)
Maintenance of a quiescent and organotypically-differentiated layer of blood vessel-lining endothelial cells (EC) is vital for human health. Yet, the molecular mechanisms of vascular quiescence remain largely elusive. Here we identify the genome-wide transcriptomic program controlling the acquisition of quiescence by comparing lung EC of infant and adult mice, revealing a prominent regulation of TGFß family members. These transcriptomic changes are distinctly accompanied by epigenetic modifications, measured at single CpG resolution. Gain of DNA methylation affects developmental pathways, including NOTCH signaling. Conversely, loss of DNA methylation preferentially occurs in intragenic clusters affecting intronic enhancer regions of genes involved in TGFβ family signaling. Functional experiments prototypically validated the strongly epigenetically regulated inhibitors of TGFβ family signaling SMAD6 and SMAD7 as regulators of EC quiescence. These data establish the transcriptional and epigenetic landscape of vascular quiescence that will serve as a foundation for further mechanistic studies of vascular homeostasis and disease-associated activation.
Published: 11 May 2018
Gesehen am 19.03.2020